The role of Allied Health Professions and Nursing Research Internships in developing a research culture: a mixed-methods exploration of stakeholder perspectives - J. Nightingale; S. Fowler-Davis; K. Grafton; S. Kelly; C. Langham; R. Lewis; B. Bianco; D. Harrop (BMC, 2020)
Abstract Background Developing research capability and capacity within the healthcare professions is a challenge throughout diverse international settings. Within England, the National Institute for Health Research aimed to address these challenges through the Integrated Clinical Academic (ICA) research careers escalator for nurses, midwives and allied health professionals. Poor academic progression has been identified in the advanced stages of the pathway, though progression from the earlier entry point (Internship) has not previously been investigated. A national evaluation of four completed Internship cohorts was undertaken to explore stakeholder perspectives and progression beyond the Internship programme. Methods A mixed methods project used sequential qualitative and quantitative data collection phases commencing with two stakeholder focus groups (n = 10); the findings informed the development of an online survey distributed to previous cohorts of interns (n = 104), their managers (n = 12) and academic mentors (n = 36). Eight semi-structured interviews subsequently explored the challenges and opportunities afforded by the internships. Thematic analysis was used to review qualitative data from focus groups and interviews, with survey data analysed and displayed using descriptive statistics. Synthesis of data from each phase is displayed within the four level evaluation framework outlined within the New World Kirkpatrick® Training Evaluation Model. Results Important regional differences exist yet the internships are highly valued by all stakeholders. Representation varied between different professions, with nursing and some service-based professions poorly represented. All interns successfully completed the programme (n = 104), with evidence of positive impacts on interns, colleagues and patient care. Balancing research commitments with clinical activity was challenging; middle managers were seen as gatekeepers to programme success. Progression to the next stage of the ICA pathway is highly competitive and was achieved by only a quarter of interns; access to mentors outside of the funded programme is vital for a successful transition. Conclusions The Internship programme succeeds in providing a range of important early experiences in research, though progression beyond the programme is challenging due, in part, to a widening gap between Internship and the next level of the ICA framework. Vital mentorship support to bridge this gap is threatened by a lack of time and funding; therefore, the pursuit of a clinical-academic career will continue to be elusive for many nurses and allied health professionals. A partnership approach to clinical academic support at institutional level is needed with several international models offering alternative strategies for consideration.